2009
DOI: 10.1016/j.sna.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Microphone based on Polyvinylidene Fluoride (PVDF) micro-pillars and patterned electrodes

Abstract: Piezoelectric materials have the ability to transfer energy between the electric and mechanical domains. Polyvinylidene fluoride (PVDF) exhibits higher piezoelectricity than other polymer materials such as nylon and polyvinyl chloride. PVDF is a superior material for sensors because its stress constant, the ability to convert stress into electrical energy, is more than 20 times higher than that of lead zirconate titanate. Nonetheless, there is significant interest in improving the effective stress constant of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 47 publications
1
56
0
1
Order By: Relevance
“…For one, there are expected differences in mechanical compliance between patterned microstructures and flat sheets. A poled PVDF micropillar is not constrained by any surrounding material along and around its sidewalls; therefore it is anticipated to exhibit more deformation in response to an electric field, in comparison to a solid PVDF sheet (Dubach et al 2009;Xu et al 2009). In addition, previous studies have also shown that the pressure and temperature-based imprinting process can lead to a improved orientation of the crystalline domains in PVDF and PVDF-TrFE films, which under certain conditions, such as electric field driven polarization, could result in improved piezoresponse (reflected in increased piezoelectric coefficients), compared to flat PVDF films (Hu et al 2005;Kang et al 2007;Liu et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, there are expected differences in mechanical compliance between patterned microstructures and flat sheets. A poled PVDF micropillar is not constrained by any surrounding material along and around its sidewalls; therefore it is anticipated to exhibit more deformation in response to an electric field, in comparison to a solid PVDF sheet (Dubach et al 2009;Xu et al 2009). In addition, previous studies have also shown that the pressure and temperature-based imprinting process can lead to a improved orientation of the crystalline domains in PVDF and PVDF-TrFE films, which under certain conditions, such as electric field driven polarization, could result in improved piezoresponse (reflected in increased piezoelectric coefficients), compared to flat PVDF films (Hu et al 2005;Kang et al 2007;Liu et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It is envisioned however that microstructured piezoelectric materials could provide improved sensitivity and functionalities to MEMS devices (Li and Bonnell 2008). Previous modeling studies suggest, for example, that micropatterned PVDF films could provide enhanced acoustic sensitivity compared to flat PVDF films (Xu et al 2009). Moreover, in regards to BioMEMS technologies, component miniaturization is important for achieving more direct interactions with biological entities at the cellular and subcellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…The Polyvinylidene Fluoride polymer (PVDF), discovered by Kawai is frequently using for sensor development in biomedical applications [14]. This material is having a homogenous and solid structure with approximately 50% − 65% crystallinit [15], [16].…”
Section: Pvdf Sensormentioning
confidence: 99%
“…Being able to increase the pillar height to diameter ratio to 4 or higher would enable the use of any amplifier input resistance and pillar heights of 15 μm or higher. Further details on the optimization procedure have been presented by Xu et al 21,22 …”
Section: Optimizationmentioning
confidence: 99%